The Use of Conceptual Metonymy in Indonesian Football News: A Cognitive Semantic Approach - Parasian, Nehemia Anugrah; Mulyadi, Mulyadi (Andalas International Journal of Socio-Humanities, 2025)
Metonymy is a form of language use in the world that is commonly used in sports discourse, especially football, to present information more concisely and expressively. This research aims to analyze the use of types of metonymy in football news and identify the dominant pattern in its use. This research uses qualitative research methods with data sources from several football websites. The data analysis used is data reduction, data presentation, and conclusion drawing. The results showed that there are seven types of metonymy found in football news, namely part for whole, producer for product, object for user, controller for controlled, institution for people responsible, place for institution, and place for event. The most dominant type of metonymy is Controller for Controlled with a percentage of 26.67%, followed by Institution for People Responsible with 20% occurrence. Furthermore, object for user is in the third position with 15% occurrence. The use of metonymy in football news is to make the delivery of information more concise, expressive, and interesting for readers. In addition, metonymy is also used to clarify the relationship between an entity and the role or action it represents, so that the news is easier to understand and has its own appeal in its writing style.